Microwave Assisted Selective Hydrolysis of Polyamides from Multicomponent Carpet Waste - Bäckström, Eva (Glob Chall, 2021)
Selective hydrolysis of polyamide‐6 (PA‐6) and polyamide‐66 (PA‐66) from commercial multicomponent PA‐6/PA‐66/polypropylene (PP) carpet is demonstrated by a microwave‐assisted acid catalyzed hydrothermal process, yielding monomeric products and solid polypropylene residue. First, an effective method is established to chemically recycle neat PA‐6 and PA‐66 granules using microwave irradiation. The optimized, hydrochloric acid (HCl) catalyzed process leads to selective production of monomers, 6‐aminocaproic acid or adipic acid and hexamethylenediamine, after only 30 min. A piece of commercial carpet is then recycled using the same reaction conditions, but with the alteration of the reaction time from 1 to 6 h. The produced water‐soluble products and the remaining solid residue are carefully characterized, proving that the polyamide‐part of the carpet is selectively hydrolyzed into water‐soluble monomers and the polypropylene‐part remains as an unconverted solid that can be further used to produce recycled filaments containing the carpet residue and virgin polypropylene. The developed process opens the possibility to recycle multicomponent materials, such as carpets, through selective hydrolysis. It can also contribute to a circular economy, producing original monomers and materials ready for a new life‐cycle.